Analyzing for-profit colleges and universities that offer bachelors, masters, and doctorates to inmates incarcerated in American correctional facilities - Ross, Jeffrey Ian (Journal of offender rehabilitation, 2015)
Postsecondary education for inmates is championed as an important path to rehabilitation and a factor minimizing recidivism. Over the past four decades, several for-profit colleges and universities have offered degree-based programs to inmates at American correctional facilities. This article reviews the history of these educational institutions, the typical inmates who enroll in these kinds of courses, the appeals that these businesses make to convicts, the channels for their advertisements, and the experiences of inmates who have enrolled and (sometimes) graduated from these courses. This study takes both an historical and an autoethnographic approach to its subject matter. The authors conclude by speculating on appropriate policy responses to for-profit postsecondary education institutions that provide this kind of service to inmates, and alternatives that may be better methods for college degree instruction and delivery in jails and prisons.